A generalised hot cracking criterion for nickel-based superalloys additively manufactured by electron beam melting - Chandra, Shubham (2021)
The influences of microstructure and solidification parameters on the hot cracking behaviour of an additively manufactured Ni-based superalloy via selective electron beam melting (SEBM) have been investigated. Severe intergranular hot cracking is found to occur at grain boundaries (GBs) in the SEBM-built superalloy. A generalised cracking criterion that considers various process parameters along with the GB inclination is developed on the basis of a prevailing hot cracking criterion for columnar-grained microstructure. A parametric evaluation of influencing factors is quantitatively conducted to predict the optimal conditions that could prevent hot cracking while maintaining the desirable fine microstructure. With the aid of numerical simulations, it is determined that while micro-segregation occurs at all types of GBs, its occurrence at the divergent ones tend to promote cracking. Using the results of this work, hot cracking in additively manufactured Ni-based superalloy single crystals can be potentially mitigated.